“Propuesta de un sistema de gestión de inventarios para el taller automotriz “Victor Nuñez” - Nuñez Merino, Jonathan Vinicio (2023)
The automotive workshop "Víctor Nuñez" is located in the city of Ambato and is dedicated to providing repair and maintenance services for all types of vehicles, whether diesel or gasoline engines, in this company specifically in the area of warehouse, it was identified that the spare parts that are used when carrying out maintenance services have not been inventoried or controlled, which makes it difficult to locate them or, in due case, that they are not available due to their non-existence or the existence of a excess spare parts in this area, thus leading to a certain delay in the delivery of the work. As a proposed solution to this problem, the study of the implementation of an inventory management system was carried out, using the ABC model, the economic order quantity model, with safety stock and probabilistic reorder point in order to avoid shortages and overloads in the stock, and in this way prevent loss of customers due to the delay of the service.